Competencies and teaching effectiveness in social sciences at Indian agricultural universities - MAHRA, GIRIJESH SINGH; KASHYAP, S K; SINGH, PREMLATA; JOSHI, PRATIBHA; GUPTA, SHWETA (The Indian Journal of Agricultural Sciences, 2020)
In India, teaching, research and extension are the three pillars of National Agricultural Research and Education System (NARES) in which agricultural extension connects agricultural research and farmers. Teaching in agricultural extension discipline across agricultural universities at postgraduate level prepares extension professionals to conduct need based research and transfer relevant technologies to farming community. The present study primarily focuses on assessing the overall teaching effectiveness of agricultural universities with respect to extension education discipline in order to understand the competence level of extension graduates from Indian agricultural universities. The investigation is based on primary data compiled from 66 teachers engaged in teaching of extension education discipline and 210 postgraduate (M Sc and Ph D) students across 10 agricultural universities of Northern India. It was found that majority of the students (64.29%) perceived that overall acquisition of essential extension competencies is low, while only 10.94 percent of students perceived it to be high. Out of the 10 universities examined for teaching effectiveness, six had medium teaching effectiveness, while two universities had high and two universities had low teaching effectiveness. The overall teaching effectiveness index of all 10 universities was 0.607 indicating a teaching effectiveness of above average. The present study therefore identified those essential extension competencies which need emphasis in the extension education teaching-learning scenario. The teaching effectiveness index developed can be used by agricultural universities to assess teaching effectiveness of extension education teachers.